FRI0033 TNFalpha Production In Cultured Human Macrophages after CTLA4-IG (abatacept) In Vitro Treatment. (15th July 2016) - Brizzolara, R.; Montagna, P.; Soldano, S.; Trombetta, A.C.; Paolino, S.; Pizzorni, C.; Sulli, A.; Ruaro, B.; Camellino, D.; Tomatis, V.; Cutolo, M.
Abstract : Background: Proinflammatory cytokines and particularly tumor necrosis factor alpha (TNFalpha) are abundantly expressed in rheumatoid arthritis (RA) synovitis. Our recent data showed that CTLA4-Ig (abatacept), by interacting with the CD86 molecule on RA synovial macrophages, may induce reverse signaling with anti-inflammatory effects, involving NFkB intracellular pathway [1–4]. Objectives: We investigated the expression and production of TNFalpha on cultured human activated macrophages before and after in vitro CTLA4-Ig treatment. Methods: THP-1 human monocytes, differentiated with phorbol myristate acetate (0.05 μg/ml for 24 hrs) into activated macrophages, were cultured in multiwells bottoms or flexiperm slides for 3, 24 and 48 hrs, in the absence (cells untreated) and in the presence of CTLA4-Ig (500 μg/ml). TNFalpha gene expression was investigated by quantitative real time polymerase chain reaction (qRTPCR), after 3 and 24 hrs from CTLA4-Ig treatment. Intracytoplasmatic TNFalpha protein expression was investigated by immunocytochemistry (ICC) analysis after 24 and 48 hrs from treatment. Extracellular TNFalpha production was evaluated in the culture surnatants, by immunoassay (ELISA) analysis, after 24 hrs from treatment. Experiments were done in triplicate. Results: Interestingly, at gene level, qRTPCR showed already after 3 hrs (and 24 hrs) from CTLA4-Ig treatment a significant downregulation of TNFalpha gene expression (p<0.05 for both 3 and 24 hrs), compared to the untreated cells. ICC analysis showed that TNFalpha production resulted decreased (not significant) both after 24 hrs and 48 hrs from CTLA4-Ig (500 mg/ml) treatment, compared to the untreated cells. Extracellular evaluation by ELISA at 24 hrs, also demonstrated a reduction (not significant) of TNFalpha levels, compared to the untreated condition. Conclusions: In cultured activated macrophages TNFalpha production was significantly reduced by CTLA4-Ig in vitro treatment at gene level, already after 3 hrs and still evident at 24 hrs. Regarding the protein synthesis, as expected, a trend for their reduction was observed on longer time (24–48 hrs). References: Cutolo M et al. Arthritis Res Ther 2009, 11:176–85. Brizzolara R et al. Reumatismo 2011, 63:80–5. Brizzolara R et al. J Rheumatol 2013;40(5):738–40. Cutolo M et al. Clin Exp Rheumatol 2013;31(6):943–6. Disclosure of Interest: R. Brizzolara: None declared, P. Montagna: None declared, S. Soldano: None declared, A. C. Trombetta: None declared, S. Paolino: None declared, C. Pizzorni: None declared, A. Sulli: None declared, B. Ruaro: None declared, D. Camellino: None declared, V. Tomatis: None declared, M. Cutolo Grant/research support from: Research grant by Bristol Myers Squibb